Hyperemesis Gravidarum in the context of migration: when the absence of cultural meaning gives rise to "blaming the victim" - Danielle Groleau; Jessica Benady-Chorney; Alexandra Panaitoiu; Vania Jimenez (BMC, 2019)
Abstract Background Hyperemesis gravidarum (HG) is a rare complication of pregnancy that involves persistent nausea and extreme vomiting to an intensity that differentiates HG from nausea and vomiting commonly experienced during pregnancy. Research has suggested potential biological and psychological etiological pathways for HG, but the augmented prevalence in immigrant populations, which is 4.5 times higher, remains unclear. Studies show that in order to better address the psychosocial needs of immigrant patients with HG, we must first improve our understanding of how they experience their illness. The objective of this study was to understand the meaning and experience of HG among immigrant women in Canada. Methods Our "qualitative comparative analysis design" involved a sample of 15 pregnant mothers following their hospitalization for HG, including 11 immigrant women and 4 Canadian-born women recruited for comparison purposes. We used the Edinburgh Perinatal Depression Scale to assess distress, and the McGill Illness Narrative Interview Schedule to explore how pregnant women understood and experienced their HG and the health services that they received. Results With the exception of a few women whose mothers suffered from HG, immigrant women and their loved ones did not have cultural knowledge to attribute meaning to HG symptoms. This left them vulnerable to criticism from family, as well as feelings of self-doubt, stress, and anxiety. We interpret this phenomenon as 'victim blaming'. Immigrant women's experience of HG was also characterised by high levels of depressive symptoms (40%) which they linked to the severity of their symptoms, high levels of stress associated with adapting to their new country, social isolation, and loss of female family members. Furthermore, in contrast to Canadian-born women, immigrant women frequently reported feeling that their symptoms were minimized by hospital emergency room medical staff, which led to delays in obtaining appropriate health care. However, once admitted to hospital, they perceived the care provided by dieticians and nurses as helpful in managing their symptoms. Conclusions Wider awareness of the impact of HG may improve the quality of family support for immigrant women. There is a need to improve the delays and appropriateness of clinical care.